Impact of Personality Trait of Emotional Stability on Oral Parafunctional Habits - Hira Butt; warda Athar; Taimur Hassan Shah; Tajwar Jafar; Nauman Rauf Khan; Amna Zahid; maria Jabbar (Gandhara University, 2023)
OBJECTIVES To find the impact of emotional stability on oral parafunctional habits. METHODOLOGY A Cross-sectional descriptive study was conducted at the College of Dentistry, Sharif Medical and Dental College, Lahore, over five months, from July to November 2021. Data was collected using a medical questionnaire and a ten-item personality inventory scale (TIPI). The medical questionnaire comprised two sections with 11 items. The first section had six demographic statements, including age, gender, marital status, occupation, educational level and medical condition. The second section consisted of a pre-validated parafunctional habits questionnaire. RESULTS There was a non-significant difference in the scores of the personality trait of emotional stability across categories of oral parafunctional habits of nail-biting (p=0.093), tooth grinding (p=0.192), tooth clenching (p=0.055), biting on hard objects (p=0.17) and chewing gum (p=0.116). CONCLUSION Emotional stability was most prevalent in individuals who denied having the habit of nail-biting, teeth grinding, tooth clenching and biting hard objects but neither agreed nor disagreed with having the habit of chewing gum.